Language is for thought and communication - Martina Wiltschko (Glossa, 2022)
There is an ancient debate about whether language is an instrument for thought or for communication. I argue that the distinction is misleading, and that language is an integral part of both, human-specific thought, and communication. The argument is based on the growing consensus that grammatical knowledge – a hallmark of human language – encompasses not only the propositional content of an utterance but also its communicative content. If communicative content is regulated by grammatical knowledge, then it follows that communication is as much a function of language as thought is.